MATERNAL AND FETAL OUTCOME OF PREGNANCY IN SLE: A SINGLE CENTER SURVEY FROM PAKISTAN - MUNIR , S; MUSHTAQ , S; AMIN , J; SIDDIQUE , S; JAMIL , S; AWAIS , MA (Biological and Clinical Sciences Research Journal, 2024)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease with multifactorial origins, affecting multiple organ systems. Pregnancy in women with SLE is associated with a higher risk of complications and adverse outcomes. This study aimed to evaluate maternal and fetal outcomes in pregnant patients with SLE. Objective: To analyse the maternal and fetal pregnancy outcomes in patients with SLE. Methods: This cross-sectional study was conducted over six months, from Jan 2024 to July 2024, after approval from the institutional ethical review board. Sixty-six pregnant women with SLE were enrolled based on specific inclusion and exclusion criteria. Detailed medical histories were collected, and patients were followed throughout pregnancy for maternal and fetal outcomes. Data was analyzed using SPSS version 26.0. Results: The mean age of the participants was 35.11 ± 7.27 years. Maternal complications included SLE flare in 47 (71.2%) patients, onset of disease during pregnancy in 4 (6.1%) patients, and normal pregnancy in only 15 (22.7%) cases. Fetal outcomes revealed intrauterine growth retardation (IUGR) in 12 (18.2%) cases and intrauterine death in 5 (7.6%) cases. Conclusion: Pregnancy in women with SLE is associated with significant maternal and fetal complications. The high prevalence of adverse outcomes underscores the need for careful monitoring and specialised care during pregnancy to improve prognoses.